Synthesis and Characterization of New Mono-and Bis-Schiff Bases - HAYVALI, ZELIHA (Asian Journal of Chemistry, 2010)
New Schiff base derivatives were prepared by the condensation of 3,4-dihydroxybenzaldehyde and 2,4,5 trihydroxybenzaldehyde with 4-amino-1 ,2-dihydro-1 ,5-dimethyl-2-phenyl-3H-pyrazole-3-one (4-amino-phenazone, 4-aminoantipyrine, 4-AAP) (4 and 5). 2,2'-[1,2-Phenylenebis(methyleneoxy)]dibenzaldehyde (3) was prepared by the reaction of 1,2-bis(bromomethyl)benzene and salicylaldehyde. Condensation reactions between the dialdehyde (3) with 4-aminoantipyrine and 2-aminomethylfuran (furfurylamine) yielded the new Schiff base ligands 6 and 7. The structures of these compounds were confirmed on the basis of elemental analyses, IR, 1H and 13C NMR and mass spectroscopic data.